1997
DOI: 10.1111/j.1600-079x.1997.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm in experimental granulomatous inflammation is modulated by melatonin

Abstract: Biological rhythms are detected in a variety of physiological and pathological conditions in man and animals, such as rheumatoid arthritis and asthma. Here we describe a circadian rhythm in experimental infectious and non-infectious granuloma. After 30 days of BCG (Bacillus Calmette-Guerin) or nystatin inoculation in the left hind foot of C57B1/6 mice, there is an oscillation with a period of approximately 24 hr in the variation of paw thickness, indicating a circadian rhythm. The acrophase occurred during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
21

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 23 publications
4
44
0
21
Order By: Relevance
“…40 In the present studies, leakage of the Evans blue dye underwent a time-dependent variation in the mouse. Indeed, variation in genes relevant to barrier function may contribute not only to diurnal variation in edema accumulation 41,42 but also to the diurnal variation in severity of inflammatory syndromes, such as bronchial asthma 43 and arthritis. 44 Inclusion of genes relevant to vascular integrity and response to injury in the oscillating subset raise the possibility that the dysplastic response to injury, which contributes to restenosis after percutaneous angioplasty, might be conditioned by the timing of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…40 In the present studies, leakage of the Evans blue dye underwent a time-dependent variation in the mouse. Indeed, variation in genes relevant to barrier function may contribute not only to diurnal variation in edema accumulation 41,42 but also to the diurnal variation in severity of inflammatory syndromes, such as bronchial asthma 43 and arthritis. 44 Inclusion of genes relevant to vascular integrity and response to injury in the oscillating subset raise the possibility that the dysplastic response to injury, which contributes to restenosis after percutaneous angioplasty, might be conditioned by the timing of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bearing in mind that (a) endothelial-derived NO mediates neutrophil adherence (Schaefer et al, 1998); (b) L-NAME inhibits vascular permeability induced by vascular endothelial growth factor (Murohara et al, 1998); (c) caveolin-1 knockout mice exhibit an increased vascular permeability (Schubert et al, 2002); and (d) mesenteric and cremaster microvascular hypermeability is blunted in eNOS knockout mice (Hatakeyama et al, 2006), we could propose that eNOSderived NO is linked to the early steps of the inflammatory response and that melatonin would also regulate this function. We have already shown that low doses of melatonin inhibit paw oedema in a model of chronic inflammation in mice (Lopes et al, 1997) and vascular permeability induced by leukotriene B 4 (Lotufo et al, 2006).…”
mentioning
confidence: 99%
“…Bradykinin, ATP and histamine are involved in mechanisms such as immune responses, inflammation and endothelial-mediated vasodilatation, with some of these actions being mediated by NO (Hill et al, 1997;Kunapuli and Daniel, 1998;Leeb-Lundberg et al, 2005;Burnstock, 2006). In addition, an immunomodulatory role of melatonin has been proposed (Lopes et al, 1997;Pontes et al, 2006). Thus, bearing in mind that (a) endothelial-derived NO mediates neutrophil adherence (Schaefer et al, 1998); (b) L-NAME inhibits vascular permeability induced by vascular endothelial growth factor (Murohara et al, 1998); (c) caveolin-1 knockout mice exhibit an increased vascular permeability (Schubert et al, 2002); and (d) mesenteric and cremaster microvascular hypermeability is blunted in eNOS knockout mice (Hatakeyama et al, 2006), we could propose that eNOSderived NO is linked to the early steps of the inflammatory response and that melatonin would also regulate this function.…”
mentioning
confidence: 99%
“…Esta ritmicidade não é observada em camundongos pinealectomizados. O padrão do processo inflamatório é restaurado após reposição de melatonina, em doses farmacológicas, adicionada à água, oferecida apenas na fase de escuro 15,16 . Por outro lado, em inflamação alérgica pulmonar, asma brônquica, a melatonina apresenta efeito pró-inflamatório 17 .…”
Section: Melatonina E As Respostas De Defesa Do Organismo (Respostas unclassified